Efektivitas Edukasi Kesehatan Berbasis Media Digital terhadap Pengetahuan Kesehatan Remaja - Putra, Juniawan mandala; Oktan, Almadea Faldisa; Meinorizah, Meinorizah (CV, Akira Java Bulu, 2026)
The rapid development of digital technology has transformed the way adolescents access health information. Young people increasingly utilise digital media such as social media platforms, health applications, and online learning platforms as primary sources of health-related information. This study aims to analyse the effectiveness of digital media–based health education in improving adolescents’ health knowledge. The research employed a mixed methods approach using a sequential explanatory design, integrating both quantitative and qualitative methods to provide a comprehensive understanding of the phenomenon. Quantitative data were collected through pre-test and post-test questionnaires administered to 120 senior high school students in Jakarta who participated in a four-week digital health education programme delivered through social media platforms and educational videos. The quantitative data were analysed using a paired sample t-test to measure differences in health knowledge before and after the intervention. Subsequently, qualitative data were obtained through in-depth interviews with 15 participants to explore their experiences and perceptions regarding the use of digital media in health education. The qualitative data were analysed using thematic analysis. The results indicate a significant improvement in adolescents’ health knowledge after participating in the digital health education programme (p < 0.05). Qualitative findings reveal that digital media were perceived as engaging, easily accessible, and effective in helping adolescents understand health information in a more interactive manner. However, several participants emphasised the importance of verifying the credibility of health information sources in order to prevent misinformation. This study concludes that digital media–based health education is an effective strategy for improving adolescents’ health knowledge and can serve as an innovative approach for health promotion by nursing professionals in the digital era.